PENERAPAN MEDIA PEMBELAJARAN MOGE 630 DAPAT MENINGKATKAN HASIL BELAJAR GEOGRAFI DI KELAS XII IPS MAN 1 KOTA PADANG PANJANG - Nelvarita BR Nelvarita (JURUSAN GEOGRAFI FIS UNP, 2020)
Abstract This learning innovation starts from students' anxiety in facing the National Examination Class XII IPS MAN 1 Padang Panjang City. On Geography. This innovation aims to help improve learning outcomes in Geography and motivate student learning activities in learning and solving questions on the National Examination by using MOGE 630 / Geography Monopoly learning media. This innovation was carried out in class XII IPS MAN 1 Kota Padang Panjang. Data collection techniques with observation, documentation, tests and quizzes. Data analysis conducted in this study was the presentation of data and drawing conclusions. The results of this study indicate that the use of the Geography Monopoly learning media is able to overcome the anxiety of students in facing the National Examination, this can be seen from the results of learning Geography in class XII IPS MAN 1 Padang Panjang. Experienced an increase in students' learning completeness in each quiz results, namely (82.46 .%) By using MOGE 630 learning media / Monopoly of Geography students find Geography learning very exciting, fun and feel the cases and questions and the material presented feels light.